The Impact of Electronic Applications on Attracting Customers to Electronic Sales Stores of Cosmetic Products - Mohammad Jamal Abu-Alruz (Politeknik Siber Cerdika Internasional, 2024)
This study aims to identify the impact of electronic applications with dimensions in attracting customers with dimensions to beauty product e-stores. An analytical descriptive approach is used to match the research problem and objectives. The research population includes all electronic shops that sell beauty products in the city of Amman, totaling 21 stores that specialize in selling beauty products. The research respondents were 21 managers, 42 heads of departments, and 131 marketing employees. The program (SPSS) is used for statistical analysis and research hypothesis testing. This study found that there is a statistically significant positive impact at the significance level (??0.05) for the impact of electronic applications with their dimensions (social media applications, mobile applications, e-marketplace applications, and email applications) in attracting customers with their dimensions (interaction process , value creation, emotional attachment) of the beauty product e-shop, and also found a positive impact on the significance level (??0.05) of e-application in its combined dimension on attracting customers only, i.e. interaction process, value creation, emotional attachment) of Beauty product e-shop. This study recommends several recommendations, and the most numerous are: The need to expand the use of social media applications, including YouTube, because of the technical capabilities of these applications in serving promotional advertisements in the form of images and videos produced with interesting artistic techniques. to attract the attention and interest of customers to arouse their feelings, feelings and emotions towards their beauty products and brands with the aim of purchasing.